If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7h-19=2h+17
We simplify the equation to the form, which is simple to understand
-7h-19=2h+17
We move all terms containing h to the left and all other terms to the right.
-7h-2h=+17+19
We simplify left and right side of the equation.
-9h=+36
We divide both sides of the equation by -9 to get h.
h=-4
| X^3+3x^2+x= | | 3(m+12)+20=5 | | (6)3=216 | | 9n=7n+49 | | 40=x+35 | | 9e^2=66.5 | | -10(s+5)=-53 | | -4n-8=4(-3n+2) | | 9e^1=16 | | 25x-(8)=22x+10 | | 4x(5x+1)=5x+1 | | 2x=x-(8) | | 8r-7=2r+35 | | 16x+8x=10 | | 18y+-x=-25 | | 3x-4=1x | | 1600x+800y=1000 | | y=1.38(3.5)-0.52 | | Y+4=3(x-2) | | -x+18y=-25 | | 7-2*2+(8-6)= | | 5x+14.5=0 | | -9(x-(9))=3(x+47) | | 17=k-2 | | -12(x-(9))=3(x+16) | | -5(z+1)=-2z+10 | | 3Xsquared+5X=0 | | 1.4=n-2 | | -7x-(2.8)=6x-(13.2) | | 9s+9=30 | | 7x-(2.7)=-6x-(7.9) | | 8S-23=-14+5S |